Pengenalan Artificial Intelligence Pada Pondok Pesantren Yatim Al Ikhsan Surakarta - Budi Al Amin; Candra Agustina; Wawan Haryanto; Galih Setiawan Nurohim (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Introduction and use of artificial intelligence (AI) technology is increasingly widespread in various aspects of human life. In the context of community service, AI has great potential to improve the quality of life of people through a variety of innovative applications. This article discusses how AI can be used in community service, including practical applications in the field of education. Student Data Management: Al Ihsan Foundation can use AI to manage orphan student data such as personal data, academic data, and health data. AI-supported data management systems can integrate this information better, thus enabling more personalized and customized services. Learning and Development: AI can be used to develop online learning platforms that are tailored to individual student learning needs. AI systems analyze student learning preferences and progress and recommend the most effective learning materials and methods. By leveraging AI, younger generations can create exciting, high-quality content without having to have specialized expertise in graphic design or video editing. For example, technologies such as Canva Magic Studio leverage artificial intelligence to make it easier to make exciting designs.The training aims to provide a better understanding to the younger generation of the basic concepts of AI and its applications in everyday life, including in the creation of creative digital content. Hopefully, with a better understanding of AI, the younger generation will be able to develop their creative potential and use it for a variety of positive purposes in their lives.